Analysis of the Alignment Between the Aqidah Curriculum of PKPPS Ibnu Abbas As Salafy Sragen and the Ministry of Religious Affairs Curriculum - Purwoko, Sahid; Sukari, Sukari (Universitas Islam Negeri Sumatera Utara, 2025)
The curriculum of Aqidah subject at Pondok Pesantren Ibnu Abbas As Salafy Sragen has distinctive characteristics differing from the 2013 Curriculum implemented by the government. This study aimed to analyze the alignment between the pesantren's curriculum and the national curriculum and identify challenges faced in the integration process. This study used a qualitative approach with a descriptive method to explore and describe the differences and alignments between the pesantren’s curriculum and the 2013 Curriculum. Data were collected through interviews, observations, and document analysis. The obtained data were analyzed to identify gaps and challenges in curriculum implementation. The findings indicate that while there is alignment in the content of Aqidah teaching between the pesantren and the 2013 Curriculum, there are significant differences in teaching methods and evaluation systems. Teaching methods in the pesantren's traditional, that focusing on memorization and lectures, need to be adapted to the student-centered learning approach recommended in the 2013 Curriculum. Additionally, a more comprehensive and varied evaluation system is required to reflect various aspects of student development according to national standards. The main challenges are resistance to change, limited resources, and the need for teachers.